Absolute and attributable risks of atrial fibrillation in relation to optimal and borderline risk factors: The atherosclerosis risk in communities (ARIC) study - Huxley, Rachel; Lopez, F.; Folsom, A.; Agarwal, S.; Loehr, L.; Soliman, E.; Maclehose, R.; Konety, S.; Alonso, A. (2011)
Background: Atrial fibrillation (AF) is an important risk factor for stroke and overall mortality, but information about the preventable burden of AF is lacking. The aim of this study was to determine what proportion of the burden of AF in blacks and whites could theoretically be avoided by the maintenance of an optimal risk profile. Methods and Results: This study included 14 598 middle-aged Atherosclerosis Risk in Communities (ARIC) Study cohort members. Previously established AF risk factors, namely high blood pressure, elevated body mass index, diabetes mellitus, cigarette smoking, and prior cardiac disease, were categorized into optimal, borderline, and elevated levels. On the basis of their risk factor levels, individuals were classified into 1 of these 3 groups. The population-attributable fraction of AF resulting from having a nonoptimal risk profile was estimated separately for black and white men and women. During a mean follow-up of 17.1 years, 1520 cases of incident AF were identified. The age-adjusted incidence rates were highest in white men and lowest in black women (7.45 and 3.67 per 1000 person-years, respectively). The overall prevalence of an optimal risk profile was 5.4% but varied according to race and gender: 10% in white women versus 1.6% in black men. Overall, 56.5% of AF cases could be explained by having =1 borderline or elevated risk factors, of which elevated blood pressure was the most important contributor. Conclusion: As with other forms of cardiovascular disease, more than half of the AF burden is potentially avoidable through the optimization of cardiovascular risk factors levels. © 2011 American Heart Association, Inc.